Self-management of mood and/or anxiety disorders through physical activity/exercise - Pelletier, Louise (Health Promot Chronic Dis Prev Can, 2017)
INTRODUCTION: Physical activity/exercise is regarded as an important self-management strategy for individuals with mental illness. The purpose of this study was to describe individuals with mood and/or anxiety disorders who were exercising or engaging in physical activity to help manage their disorders versus those who were not, and the facilitators for and barriers to engaging in physical activity/exercise. METHODS: For this study, we used data from the 2014 Survey on Living with Chronic Diseases in Canada—Mood and Anxiety Disorders Component. Selected respondents (n = 2678) were classified according to the frequency with which they exercised: (1) did not exercise; (2) exercised 1 to 3 times a week; or (3) exercised 4 or more times a week. We performed descriptive and multinomial multiple logistic regression analyses. Estimates were weighted to represent the Canadian adult household population living in the 10 provinces with diagnosed mood and/or anxiety disorders. RESULTS: While 51.0% of the Canadians affected were not exercising to help manage their mood and/or anxiety disorders, 23.8% were exercising from 1 to 3 times a week, and 25.3% were exercising 4 or more times a week. Increasing age and decreasing levels of education and household income adequacy were associated with increasing prevalence of physical inactivity. Individuals with a mood disorder (with or without anxiety) and those with physical comorbidities were less likely to exercise regularly. The most important factor associated with engaging in physical activity/exercise was to have received advice to do so by a physician or other health professional. The most frequently cited barriers for not exercising at least once a week were as follows: prevented by physical condition (27.3%), time constraints/too busy (24.1%) and lack of will power/self-discipline (15.8%). CONCLUSION: Even though physical activity/exercise has been shown beneficial for depression and anxiety symptoms, a large proportion of those with mood and/or anxiety disorders did not exercise regularly, particularly those affected by mood disorders and those with physical comorbidities. It is essential that health professionals recommend physical activity/exercise to their patients, discuss barriers and support their engagement.